2017
DOI: 10.4314/afrrev.v11i2.18
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Microteaching in Developing Teaching Skills among Pre-Service Teachers in Alvan Ikoku College of Education Owerri, Nigeria

Abstract: Teaching skills are necessary tools teachers should possess for effectiveness in their job. Teaching the teacher candidates these skills is not simple hence the need for a microteaching environment which enables pre-service teachers to acquire them under controlled laboratory setting. This study was an extension of current NCE microteaching programme run by Alvan Ikoku College of Education for the B.Ed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 3 publications
0
17
1
Order By: Relevance
“…On the whole, microteaching was found to be an effective teaching technique in the training of Indexed African Journals Online: www.ajol.info Economics student teachers. Other researchers (e.g., Mahmud and Rawshon, 2013;Musa, 2014;Onwuagboke et al, 2017;Umeh et al, 2015) also concluded that microteaching is useful in teacher education and contributes greatly to the learning process. In light of the study findings, there is need to employ the microteaching technique more effectively and frequently in Economics methodology courses.…”
Section: Conclusion and Recommendationsmentioning
confidence: 98%
“…On the whole, microteaching was found to be an effective teaching technique in the training of Indexed African Journals Online: www.ajol.info Economics student teachers. Other researchers (e.g., Mahmud and Rawshon, 2013;Musa, 2014;Onwuagboke et al, 2017;Umeh et al, 2015) also concluded that microteaching is useful in teacher education and contributes greatly to the learning process. In light of the study findings, there is need to employ the microteaching technique more effectively and frequently in Economics methodology courses.…”
Section: Conclusion and Recommendationsmentioning
confidence: 98%
“…Research on the influence of micro teaching on various aspects has been carried out by many researchers. The results showed that the practice of micro teaching has a positive influence on teaching skills [14] [15] [16]. According to Savas, participants' responses showed that micro-teaching video activity had a positive impact on improving participants' teaching skills [17].…”
Section: Fig 1 Lcmt Modelmentioning
confidence: 99%
“…In addition, numerous studies have been carried out on microteaching, although their main focus is on teaching performance (Bahjat, 2016;Bakir, 2014;Baştürk, 2016;Cobilla, 2014;Copeland, 1975;Donnelly & Fitzmaurice, 2011;Elias, 2018;Gödek, 2016;Kamimura & Takizawa, n.d;Onwuagboke, Osuala, & Nzeako, 2017;Punia, Miglani, & Singh, 2016;Saban & Çoklar, 2013;Shah & Masrur, 2011;Şen, 2010;Simbo, 1989). Unfortunately, studies that focus on PCK are still lacking irrespective of the fact that it is extremely important for pre-service teachers because it aids them to effectively carry out the instructional processes.…”
Section: Introductionmentioning
confidence: 99%